Поняття та види форм діяльності Державної служби України з лікарських засобів та контролю за наркотиками - Птухіна, О. В.; Ptukhina, O. V. (Наше право. - 2023. - № 3. - С. 77-84, 2023)
Визначено сутність форм діяльності Державної служби України з лікарських засобів та контролю за наркотиками, здійснено характеристики їх окремих різновидів. Запропоновано під формами діяльності Державної служби України з лікарських засобів та контролю за наркотиками розуміти закріплений у положеннях національного законодавства зовнішній прояв діяльності Державної служби України з лікарських засобів та контролю за наркотиками та її посадових осіб, спрямований на реалізацію державної політики у сферах контролю якості та безпеки лікарських засобів, медичних виробів, а також обігу наркотичних засобів, психотропних речовин і прекурсорів. Виокремлено дві групи форм діяльності Державної служби України з лікарських засобів та контролю за наркотиками залежно від наслідків, які спричиняє їх реалізація. До першої належать ті, що мають юридично значимі наслідки або ж правові форми діяльності Державної служби України з лікарських засобів та контролю за наркотиками, а до другої віднесено організаційні, тобто такі, що не мають своїм наслідком настання юридично значимих результатів, мають допоміжний характер і , як правило, передують застосуванню правових форм.

It has been emphasized that determining the essence of the forms of activity of the State Service of Ukraine for medicinal products and drug control, carrying out the characterization of their individual varieties will allow not only to establish the features of the external manifestation of the exercise of power by this body of state power, but also to find out the most “weak” places of such activity , to form possible options for their “strengthening” and, in general, to improve certain aspects of state policy in the field of quality and safety control of medicinal products and circulation of narcotic drugs. An analysis of the semantic-etymological and legal interpretation of the term “form” has been carried out. It has been established that the forms of activity of the State Service of Ukraine for medicinal products and drug control indicate several aspects: its subjective perception, that is, its external expression; to the sphere of social relations within which the corresponding form is applied; on the direction and method of implementation of such activity; on the circle of subjects of social relations that arise and find their development within the limits of the implementation of the corresponding form; on the scope of powers that can be exercised by the State Service of Ukraine for Medicinal Products and Drug Control within the appropriate form of its activity. It has been suggested that the forms of activity of the State Service of Ukraine for Medicinal Products and Drug Control should be understood as the external manifestation of the activities of the State Service of Ukraine for Medicinal Products and Drug Control and its officials, established in the provisions of national legislation, aimed at the implementation of state policy in the areas of quality control and safety of medicinal products. means, medical products, as well as circulation of narcotic drugs, psychotropic substances and precursors. Two groups of forms of activity of the State Service of Ukraine for medicinal products and drug control have been distinguished, depending on the consequences caused by their implementation. The first includes those that have legally significant consequences or the legal forms of activity of the State Service of Ukraine for Medicinal Products and Drug Control, and the second includes organizational ones, that is, those that do not result in legally significant results, have an auxiliary character and as a rule, they precede the application of legal forms.

Определена сущность форм деятельности Государственной службы Украины по лекарственным средствам и контролю за наркотиками, осуществлены характеристики их отдельных разновидностей. Предложено под формами деятельности Государственной службы Украины по лекарственным средствам и контролю за наркотиками понимать закрепленное в положениях национального законодательства внешнее проявление деятельности Государственной службы Украины по лекарственным средствам и контролю за наркотиками и ее должностных лиц, направленное на реализацию государственной политики в сферах контроля качества и безопасности лекарственных средств, медицинских изделий, а также обращения наркотических средств, психотропных веществ и прекурсоров. Выделены две группы форм деятельности Государственной службы Украины по лекарственным средствам и контролю за наркотиками в зависимости от последствий, вызванных их реализацией. К первой относятся имеющие юридически значимые последствия или правовые формы деятельности Государственной службы Украины по лекарственным средствам и контролю за наркотиками, а ко второй отнесены организационные, то есть не имеющие своим следствием наступление юридически значимых результатов, носят вспомогательный характер и , как правило, предшествуют применению правовых форм.
Concepts and types of forms of activity of the State Service of Ukraine for medicinal products and drug control
Keywords: Державна служба України з лікарських засобів та контролю за наркотиками; State Service of Ukraine for Medicinal Products and Drug Control; Государственная служба Украины по лекарственным средствам и контролю за наркотиками; правова форма діяльності; legal form of activity; правовая форма деятельности; організаційна форма діяльності; organizational form of activity; организационная форма деятельности; Держлікслужба; Україна; Ukraine; Украина